Library resources as correlates of students' achievement in secondary school physics: a study in school effectiveness (2009)
One of the indicators of school effectiveness is students' achievement. Unfourtunatly, students' achievement at the end of secondary school education in virtully all subjects especially physics. One of the resources that could increase students; achievement is library resources, therefore, this study sought to correlates the library and library activities with students'achievement in physics in Osun state. A total of 934 secondary schools physics students and 30 secondary schools principals were used as samples of the study. Descriptive statistics and multiple regression analysis were used to answer the research questions raised. Two research instruments were used in the study , these are the Physics Achievement Test (PAT) and School Questionnaire (SQ). The findings show that 6 out of the seven variables used in this study (availability of school library by students; frequency use of library by teachers; number of recommended physics textbooks in the school library by students; frequency of use of library by teachers; number of adequency of seats) contributed significally (P<0.05) to the explanation of students' achievement in physics.If libraries are provided in the library, it is likely that students' achievement in physics will improve.